2006
DOI: 10.1128/jb.00798-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genetics of the rdar Morphotype inSalmonella

Abstract: The Salmonella rdar morphotype is a distinct, rough and dry colony morphology formed by the extracellular interaction of thin aggregative fimbriae (Tafi or curli), cellulose, and other polysaccharides. Cells in rdar colonies are more resistant to desiccation and exogenous stresses, which is hypothesized to aid in the passage of pathogenic Salmonella spp. between hosts. Here we analyzed the genetic and phenotypic conservation of the rdar morphotype throughout the entire Salmonella genus. The rdar morphotype was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 69 publications
3
68
0
Order By: Relevance
“…s S activity and the rdar morphotype (red, dry and rough) (White & Surette, 2006;Dong & Schellhorn, 2010). Primarily, the authors observed a significantly lower prevalence of these two phenotypes in B2 than in B1 strains.…”
Section: Discussionmentioning
confidence: 73%
“…s S activity and the rdar morphotype (red, dry and rough) (White & Surette, 2006;Dong & Schellhorn, 2010). Primarily, the authors observed a significantly lower prevalence of these two phenotypes in B2 than in B1 strains.…”
Section: Discussionmentioning
confidence: 73%
“…The purpose of maintaining a dry environment in feed and food factories and low water activity in the finished product is to reduce pathogens, but these the Most Prevalent Poultry-associated Salmonella serotypes (MPPSTs) usually have a capacity of biofilm (BF) formation on plant surfaces, in the host organism, as well as in a variety of materials commonly used in the poultry production and feed industry (Steenackers et al, 2012;White and Surette, 2006). Hence, BF formation is a common feature of bacteria and it is characterized as a complex surface associated community of microorganisms.…”
Section: B I O F I L M F O R M I N G C a Pa C I T Y O F Salmonella Spmentioning
confidence: 99%
“…The rugose morphology is considered to help Vibrio and Salmonella survival in the stressful environments (White and Surette, 2006). In this study, we identified and defined rugose and smooth phenotypes in C. sakazakii.…”
Section: Detection Of Flagella Genes In the Rugose And Smooth Pairsmentioning
confidence: 90%